Вплив інноваційних засобів навчання на якість вищої освіти (на прикладі спеціальностей 241 "Готельно-ресторанна справа" та 242 "Туризм") - Чайка, Тетяна Юріївна (My University, 2023)
Досліджено теоретичні та практичні аспекти вибору заснованих на використанні інформаційних технологій засобів і інструментів навчання та викладання (на прикладі спеціальностей 241 «Готельно-ресторанна справа» та 242 «Туризм») у контексті забезпечення якості вищої освіти.

Theoretical and practical aspects of choosing the techniques and tools of learning and teaching based on information technologies (on the example of specialities 241 "Hotel and Restaurant Business" and speciality 242 "Tourism") in the context of quality assurance of higher education are explored.
The influence of innovative means of the educational process on the quality of higher education (on the example of majors 241 "Hotel and restaurant business" and 242 "Tourism")
Keywords: якість освіти; засоби навчання; цифрові інструменти; туризм; гостинність; екскурсійний маршрут; quality of education; learning techniques; digital tools; Google Maps; tourism; hospitality; sightseeing tour route